El Impacto que Genera las Redes Sociales en el Rendimiento Escolar de los Estudiantes de Noveno y Décimo Año de Educación Básica de la Unidad Educativa Municipal Héroes del Cenepa de la Ciudad de Loja y la Intervención del Trabajador Social - Llanez Alvarez., Rocio Mirian (2016)
The present investigation is part of the study on the misuse of social networks and their influence on the academic performance of students Ninth and Tenth Year Basic Education. Both overall and specific objectives posed disclose the causes and effects of misuse of social networks and the impact generated in relation to the academic performance of students. The main findings from field research shows that the causes for that of the misuse of social networks are the easy access to web pages through mobile phones, laptops, poor involvement of parents in the performing tasks, many hours remain connected; causes students to adopt poor study habits, poverty reasoning, breach of duties, poor participation in class, mental drowsiness, and even lose the school year. The methodogy based on various methods, facilitated identify and relate theories related to the problem under study, which revealed that the inappropriate use of social networks in students Ninth and Tenth Year Basic Education adversely affects their teaching – learning process. Once done the field work and preliminary analysis and interpretation of data obtained, it is concluded that excessive and inappropriate use of social networks in students, has caused adopt poor study habits, breach of tasks, poverty reasoning, mental drowsiness, etc. In addition to the existence of poor knowledge by teachers on the benefits offered by social networks in schools, it became clear that there is little involvement of parents in the control and monitoring of homework students due the long working hours. 5 The importance of social Worker in Education, through roles and functions to ensure the process of joint work with the Educational Trilogy, through training, and awareness, the proper use of social networks with the development of a proposal highlights social action. It developed field research, it is recommended Educational Work with trilogy (Parents, Teachers and Students), training in the proper use of social networks in school, social, family environment; A self-motivate Teachers, Parents in assertive participation to improve the academic performance of students Ninth and Tenth Year Basic Education Municipal Education Unit Cenepa Heroes.